ANDROID-BASED ONLINE ATTENDANCE ANALYSIS ON IMPROVING DISCIPLINE AND PERFORMANCE OF EMPLOYEES AT THE PUPR COMPETENCY DEVELOPMENT CENTER, REGION I, MEDAN - Chuzaimah Batu Bara; Aisyah Citra Dewi; Nurul Hidayah (PKM-P, 2022)
Almost all institutions require employee attendance or absenteeism data, this attendance data is very important to manage because it is for the purpose of paying salaries, intensive and so on. During the current covid-19 pandemic, what is really needed is to reduce direct or indirect contact with anyone, both in the home and work environment. Presence information systems that still use fingerprint readers are quite vulnerable to the spread of this virus. Therefore it is necessary to update the attendance system to avoid touching between employees. The transition from the manual attendance system to electronic attendance is expected to achieve the goals of a government agency so that employees can work professionally. Discipline is a form of professional attitude of an employee at work, because disciplined behavior will certainly produce good performance as well. The purpose of this research is to find out how online attendance increases the discipline and performance of employees at the Regional I PUPR Competency Development Center in Medan. In this writing, the researcher uses qualitative research methods, qualitative research is descriptive research and usually uses analysis. The results of this study reveal that the online attendance system at the Competency Development Center has not been running effectively because there is still cheating when doing attendance and other obstacles such as an error server when trying to attend attendance, which requires employees to be late in filling out absences, and will be subject to salary cuts if not given a dispensation by the staff.